Effect of high pressure on structural, electrical, and optical properties of graphene-like zinc oxide (g-ZnO) structure. (May 2022) - Nazir, Muhammad Azhar; Mahmood, Tariq; Akhtar, Naeem; Hussain, Kashif; Khan, Waheed S.; Waqar, Muhammad Asad; Aleem, Fazal-E; Saeed, Aamir; Fareed-Un-Nabi Saqi, Muhammad; Raza, Jafar
Abstract: One of the most efficient strategies to facilitate the zero-bandgap challenge in graphene is to discover graphene-like materials with intrinsic electronic bandgap and tunable properties under and beyond ambient conditions. Fortunately, zinc oxide (ZnO) is an example of such materials that offer a graphene-like structure with naturally existing electronic bandgap as well as excellent properties even in its pristine format. Inspired by this motivation, this study comprehensively surveys the structural, electronic, and enhanced optical properties of graphene-like zinc oxide (g-ZnO) structure at ambient and high-pressure conditions. As a result, it is found that the g-ZnO is a direct bandgap semiconductor material, and its bandgap values can be tuned to higher ranges under the effect of hydrostatic pressure (0–50 GPa). Additionally, the pressure-induced optical parameters are observed in good accordance with experimental measurements. Finally, this study motivates the bandgap tunability in g-ZnO to meet bandgap-related problems and new opportunities for this material in optoelectronic and photovoltaic applications.